Semaphorin 3A Increases FAK Phosphorylation at Focal Adhesions to Modulate MDA-MB-231 Cell Migration and Spreading on Different Substratum Concentrations - Scott Gehler; Frances V. Compere; Alex M. Miller (International Journal of Breast Cancer)
Interactions between integrin-mediated adhesions and the extracellular matrix (ECM) are important regulators of cell migration and spreading. However, mechanisms by which extracellular ligands regulate cell migration and spreading in response to changes in substratum concentration are not well understood. Semaphorin 3A (Sema3A) has been shown to inhibit cell motility and alter integrin signaling in various cell types. We propose that Sema3A alters focal adhesions to modulate breast carcinoma cell migration and spreading on substrata coated with different concentrations of ECM. We demonstrate that Sema3A inhibits MDA-MB-231 cell migration and spreading on substrata coated with high concentrations of collagen and fibronectin but enhances migration and spreading at lower concentrations of collagen and fibronectin. Sema3A increases focal adhesion kinase phosphorylation at tyrosine 397 (pFAK397) at focal adhesions on all substratum concentrations of collagen and fibronectin but decreased pFAK397 levels on laminin. Rho-associated protein kinase (ROCK) inhibition blocks the Sema3A-mediated effects on cell migration, spreading, and pFAK397 at focal adhesions when cultured on all concentrations of collagen. These results suggest that Sema3A shifts the optimal level of cell-matrix adhesions to a nonoptimal ECM coating concentration, in particular collagen, to yield maximal cell migration and spreading that may be mediated through a ROCK-dependent mechanism.